DEVELOPING THE CREATIVITY OF A PRIMARY CLASS TEACHER (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Orienting future specialists to innovative activities in higher education institutions, activating motivation for modern and quality education, strengthening the place and role of innovative activities in higher education, and the process of implementing educational reforms in the region's social- forecasting in accordance with the priorities of economic development is recognized as an urgent problem.